Red : a history of the redhead - Harvey, Jacky Colliss (Black Dog & Leventhal Publishers, 2015)
Stereotypes of redheaded women range from the funloving scatterbrain to the fiery-tempered vixen or the penitent prostitute. Red-haired men are often associated with either the savage barbarian or the redheaded clown. But why is this so? Harvey begins her quest in prehistory and traces the redhead gene as it made its way out of Africa with the early human diaspora, only to emerge under Northern skies. She goes on to the modern age of art, and literature, and the first positive symbols of red hair in children's characters; the genetic and chemical decoding of red hair; and finally, red hair in contemporary culture, from advertising and exploitation to "gingerism" and the new movement against bullying.